2011
DOI: 10.1007/s10570-011-9542-y
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of carboxyl groups into xylan for improved absorbency

Abstract: The objective of this research was to investigate green, renewable reaction systems for xylan that introduce crosslinking and carbonyl group for improved performance in water absorption applications. Xylan was modified separately with three different reaction agents, citric acid, succinic anhydride and sodium monochloracetate (SMCA). The xylan was reacted with citric acid in the presence or absence of sodium hypophosphite (SHP) as a catalyst, both in a solution form and in a semi-dry form in an oven. Acidbase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 26 publications
0
82
0
Order By: Relevance
“…5. Weight loss below 100°C was due to water evaporation; however, the weight loss above 100°C was caused by the thermal decomposition of the cellulose nanocrystals and fluorinated cellulose nanocrystals (Salam et al 2011). Cellulose nanocrystals have a single weight loss peak at 329.96°C, whereas polyfluorinated cellulose nanocrystals have a significant decrease in maximum weight loss temperature (286.38°C) and a significantly higher residual mass (18.5 %) after heating to 600°C.…”
Section: Resultsmentioning
confidence: 99%
“…5. Weight loss below 100°C was due to water evaporation; however, the weight loss above 100°C was caused by the thermal decomposition of the cellulose nanocrystals and fluorinated cellulose nanocrystals (Salam et al 2011). Cellulose nanocrystals have a single weight loss peak at 329.96°C, whereas polyfluorinated cellulose nanocrystals have a significant decrease in maximum weight loss temperature (286.38°C) and a significantly higher residual mass (18.5 %) after heating to 600°C.…”
Section: Resultsmentioning
confidence: 99%
“…Their work with measurement of ion diffusion rates, in addition to freeze-fracturing of hydrogels, led to the conclusion that the bulk-like water within hydrogels tended to be confined to isolated "lakes" within the pore structure. This finding suggests that various reported porous hydrogels or "foams" might be expected to contain substantial bulk-like water in addition to chemically bound water (Kabra et al 1998;Omidian et al 2005;Lu et al 2007;Chang et al 2009a,b;Sehaqui et al 2010;Salam et al 2011a). Joshi et al (2008) proposed that the relatively sharp gelation transition that takes place upon heating of methylcellulose solutions can be attributed to a thermal breakdown of the water structure, allowing coalescence of the polymer chains.…”
Section: Hydration and Hydrogen Bonding Effectsmentioning
confidence: 97%
“…A second factor that contributes to the hydrophilic nature of hemicelluloses is the content of carboxyl groups, which can dissociate to the carboxylate form at intermediate to high conditions of pH (Lindström and Carlsson 1982). Indeed, Salam et al (2011a) showed that hemicellulose could be rendered even more hydrophilic by derivatizing it to further increase the content of carboxyl groups.…”
Section: Hemicellulose and Absorbencymentioning
confidence: 99%
See 2 more Smart Citations